Proceedings of the Ninth International Conference on Tangible, Embedded, and Embodied Interaction 2015
DOI: 10.1145/2677199.2680588
|View full text |Cite
|
Sign up to set email alerts
|

VoxBox

Abstract: Gathering public opinions, such as surveys, at events typically requires approaching people in situ, but this can disrupt the positive experience they are having and can result in very low response rates. As an alternative approach, we present the design and implementation of VoxBox, a tangible system for gathering opinions on a range of topics in situ at an event through playful and engaging interaction. We discuss the design principles we employed in the creation of VoxBox and show how they encouraged wider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…These approaches can be designed to be deliberately playful in order to stimulate curiosity and intrigue. For instance, the VoxBox [18] was designed as a playful physical questionnaire that comprises a range of physical input controls, such as sliders, dials, buttons, and spinners; real-time visualisations of collected data; and a tube which delivers a ball to the users when they have completed the survey. The installation has been used to gather opinions from members of the public at a number of events such as the Tour de France in London, and has been shown to incentivise participation through the range of playful and tangible interactions it offers [18].…”
Section: Playful Physical Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches can be designed to be deliberately playful in order to stimulate curiosity and intrigue. For instance, the VoxBox [18] was designed as a playful physical questionnaire that comprises a range of physical input controls, such as sliders, dials, buttons, and spinners; real-time visualisations of collected data; and a tube which delivers a ball to the users when they have completed the survey. The installation has been used to gather opinions from members of the public at a number of events such as the Tour de France in London, and has been shown to incentivise participation through the range of playful and tangible interactions it offers [18].…”
Section: Playful Physical Computingmentioning
confidence: 99%
“…For instance, the VoxBox [18] was designed as a playful physical questionnaire that comprises a range of physical input controls, such as sliders, dials, buttons, and spinners; real-time visualisations of collected data; and a tube which delivers a ball to the users when they have completed the survey. The installation has been used to gather opinions from members of the public at a number of events such as the Tour de France in London, and has been shown to incentivise participation through the range of playful and tangible interactions it offers [18]. A similar system, Sens-Us [17] has also been used in a quite different context, to gather data for the UK census (which can include questions about more sensitive topics).…”
Section: Playful Physical Computingmentioning
confidence: 99%
“…Like other neighbourhood-scale technologies, many of these applications have been deployed in public spaces and taken advantage of their physical location, for example by capturing lightweight data from passers-by [e.g. 14,15,29,34]. Other examples of civic technologies in neighbourhoods and communities have included locative apps [13] and citizen sensing [8] and have often been grounded in DIY activities, such as fruit foraging [9], which show citizens taking an active role in shaping their environment.…”
Section: Introductionmentioning
confidence: 99%
“…By physical, we mean a bespoke interactive device that provides a range of physical input devices, such as sliders, knobs and dials that are combined with physically written questions embedded on a console. The benefits of going physical in this manner lie in their potential affordances -that can make a system appealing, attractive and obvious how to use, based on using familiar input mechanisms [9]. By standing out, we hoped it would draw in passers-by as they walked past the bureau, leading them to want to discover and know more about the SensUs.…”
Section: Introductionmentioning
confidence: 99%
“…The TexTales study further reported triggering discussions on the system and in the physical space around it [1], while with MyPosition many people stopped to look, but only one in four chose to submit an opinion [25]. Other strategies have been used to voice opinions beyond simple votes or text input, such as telephone handsets [9,27] and megaphones [7].…”
Section: Introductionmentioning
confidence: 99%